China's expanding influence in Africa: projection, perception and prospects in Southern African countries. Issue 1 (2nd January 2016) - Zhang, Xiaoling; Wasserman, Herman; Mano, Winston
ABSTRACT: China's multi-faceted endeavour to expand its influence in Africa has attracted worldwide scholarly and media attention. This article examines the different moments of China's soft power endeavour, from projection through its state media to representation and lived experiences in South Africa and Zimbabwe, two African countries which receive a significant level of attention in China's policymaking. Through interdisciplinary methodologies such as content analysis, online questionnaires and in-depth interviews conducted in China, South Africa and Zimbabwe, the authors found that China's state-engineered soft power initiatives have resulted in partial success in the two countries. The conclusions indicate that China faces many challenges in fully accomplishing its intended goal. The findings provide new insight into China's political impact in Africa within the context of Beijing's growing influence on Africa's political and economic future.